Antioxidant Activity of Leave's Extract and Isolate Ketepeng Kebo Cassia alata Linn (Leguminoceae) - Masruri Masruri; Rurini R Rurini R; Dasrul Dasrul; Aulann'iam Aulann'iam (Universitas Syiah Kuala, 2007)
Abstract. Phytochemistry and biological activity investigation of medical plants was an important step in exploring of their potency. The objectives of this research were to determine the antioxidant activity of the extract and purified isolate of C. alata leave and also, to elucidate of the molecular structure of the responsible molecule. The methods used were extraction, isolation and purification by means of chromatography, DPPH radical scavenging and spectroscopy. Result of the research provided antioxidant activity was (ED5o) 28.50±1.86 µg/mL for the extract and 9.99±0.28 µM for the purified isolate. Elucidation toward the purified isolate indicated kaemferol structure as the most active antioxidant compound. (JKS 2007; 3: 125 - 130)